2019
DOI: 10.1186/s12903-019-0783-8
|View full text |Cite
|
Sign up to set email alerts
|

Antero-posterior mandibular position at different vertical levels for mandibular advancing device design

Abstract: Introduction Mandibular Advancement Devices (MAD) have been reported to be an alternative treatment to CPAP in moderate to severe obstructive sleep apnea (OSA) cases. The design of MAD has a major influence on its success rate on the patient, and design features that have an influence on efficacy, tolerance, and compliance. The aim of this study was to determine the range of mandibular protrusion at different vertical points; 2, 5, 8 and 11 mm in a young adult population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…The present findings on MAD efficacy could be due to a lower vertical increase provided by the MB with a consequent minor post‐rotation of the mandible and a greater range of mandibular advancement. To this regard, despite Pitsis and coworkers 47 concluded that vertical opening does not influence the treatment efficacy, in a recent investigation Mayoral and coworkers 72 showed that as vertical dimension increases, the mandible rotates posteriorly, placing itself in a more retrusive location that decreases the range of mandibular advancement: as such the efficacy of the therapy could be reduced. Another hypothesis that could explain the major efficacy of MB could be attributable to the fact that it does not allow any mandibular movement, the patient is given a fixed position.…”
Section: Discussionmentioning
confidence: 98%
“…The present findings on MAD efficacy could be due to a lower vertical increase provided by the MB with a consequent minor post‐rotation of the mandible and a greater range of mandibular advancement. To this regard, despite Pitsis and coworkers 47 concluded that vertical opening does not influence the treatment efficacy, in a recent investigation Mayoral and coworkers 72 showed that as vertical dimension increases, the mandible rotates posteriorly, placing itself in a more retrusive location that decreases the range of mandibular advancement: as such the efficacy of the therapy could be reduced. Another hypothesis that could explain the major efficacy of MB could be attributable to the fact that it does not allow any mandibular movement, the patient is given a fixed position.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the design of MADs, most studies focused on the features of mono-bloc versus duo-bloc or custom-made versus prefabricated. There is no definite consensus on which design is the most effective, and a wide variety of vertical dimension of MADs were reported ranging from 1–14 mm [ 27 , 28 ]. The amount of bite opening should be minimized in the aspect of patient tolerance and treatment efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of bite opening should be minimized in the aspect of patient tolerance and treatment efficiency. Mayoral et al [ 28 ] evaluated 4 levels of vertical opening from 2 mm to 11 mm and showed that increase of vertical dimension caused retrusive position of the mandible. Similarly, a recent meta-analysis showed that the mono-bloc type showed a greater reduction in apnea/hypopnea index (AHI), and an increase in oxygen saturation compared to the effects of the duo-bloc type [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mandibular position and related structures are influenced by and participate in patency of the pharynx and the complex mechanisms that lead to obstruction of the upper airway [ 16 ]. Mandible opening during sleep causes mandibular posterior rotation [ 27 ] and is associated with a reduced cross-sectional area of the lumen [ 16 ], reduced mechanical efficiency of the pharyngeal dilator muscles [ 24 ] and increased resistance and collapsibility of the upper airway [ 14 , 21 , 28 ]. All of which may contribute to sleep-related breathing abnormalities.…”
Section: Discussionmentioning
confidence: 99%